2008
DOI: 10.1088/1748-6041/4/1/015008
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane foams electrophoretically coated with carbon nanotubes for tissue engineering scaffolds

Abstract: Carbon nanotubes (CNTs) were deposited on the surfaces of polyurethane (PUR) foams by electrophoretic deposition (EPD). The parameters of EPD were optimized in order to obtain homogeneous CNT coatings on PUR foams and adequate infiltration of the three-dimensional (3D) porous network. The microstructure of the composites was investigated by high-resolution scanning electron microscopy (HRSEM), revealing that optimal quality of the coatings was achieved by an EPD voltage of 20 V. The thermal properties of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 44 publications
0
48
0
1
Order By: Relevance
“…The researchers also show that the vascular endothelial growth factor (VEGF), a measure of the ability of materials to excite growth in cells, increases from under 50 pg/ml to over 150 pg/ml with an increase from 0 to 5 wt% MWNT content, respectively. Another observation, in the work of Zawadzak et al, shows deposition of HA crystals in electrically coated CNT-PU materials increases with increasing CNT coat thickness [59]. Control of HA crystal deposition may allow of the control of bioreactivity.…”
Section: Biomedical Applications Of Polyurethane-carbon Nanotube Compmentioning
confidence: 92%
See 2 more Smart Citations
“…The researchers also show that the vascular endothelial growth factor (VEGF), a measure of the ability of materials to excite growth in cells, increases from under 50 pg/ml to over 150 pg/ml with an increase from 0 to 5 wt% MWNT content, respectively. Another observation, in the work of Zawadzak et al, shows deposition of HA crystals in electrically coated CNT-PU materials increases with increasing CNT coat thickness [59]. Control of HA crystal deposition may allow of the control of bioreactivity.…”
Section: Biomedical Applications Of Polyurethane-carbon Nanotube Compmentioning
confidence: 92%
“…Salt leaching is a common technique in porosity preparation and this technique is capable of developing nanocomposites with specific pore size ranges and porosities. Zwadzak et al demonstrated this technique in a study that introduced NaCl crystals with widths of 300-420 and <50 µm into PU grounded at liquid nitrogen temperature and dissolved in a 1-methyl-2-pyrrolidone solution [59]. The researchers show that after moulding, 2-day immersion in water for leaching and precipitation and vacuum drying, a desirable porosity may be produced.…”
Section: Polyurethane-carbon Nanotube Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…[154,155] Therefore, an electrically conductive scaffold can stimulate bone cell growth by facilitating the physioelectrical signal transfer. [154] EPD was also used to coat CNTs onto polyurethane (PUR) foams by Zawadzak et al [157] The optimal coating in terms of the homogeneity of the coating and porosity of the scaffold after coating was achieved using a voltage of 20 V for 5 min. An acceleration of the precipitation of a weakly crystalline or amorphous calcium phosphate phase (in SBF) was observed on the CNT coated scaffolds.…”
Section: Fabrication Of Macroscale Assemblies Of Cnts Via Electrophormentioning
confidence: 99%
“…PU/CNT hybrid composites can be used as electromagnetic interference shielding materials [20] and new shape-memory materials [21]. They can also be used in biomedical devices with piezoresistive properties [18] and for tissue engineering scaffolds with nanostructured surface topography [22]. MWCNT-reinforced thermoplastic polyurethane nanocomposites have been reported to exhibit better thermal stability and mechanical performance [15].…”
Section: Introductionmentioning
confidence: 99%